Milk, meaning and morality : tracing donated breast milk from donor to baby - Waltz, Miriam H A (Social Anthropology, 2016)
This thesis follows the trajectory of donated breast milk as it leaves the dyadic mother-child relationship and is reconfigured through a series of transformations as bodily fluid, food, or medicine, depending on its context and the practices and discursive structures that seek to stabilise it as a particular object. Research was conducted between November 2014 and May 2015 in Cape Town, South Africa, including interviews with eleven donating women and eight weeks of participant observation at a level two maternity hospital. Donors use a rhetoric of 'saving babies', the effect of which is to deny the social tie between donor and recipient, or the potential for consubstantiation. Technologies play a crucial role in aiding the milk's transformation as it follows its trajectory through four nodal points (expressing and storage, pasteurisation and testing, packaging, and prescription) from donors' homes into the clinical setting, where it is framed in terms of safety and risk. Care enters into the constellation of relations that the milk ensures in unexpected ways and figures into the ways the milk is distributed in the hospital. Thus, donated breast milk shifts back and forth between being a bodily fluid, food, and medicine as its trajectory takes it through different constellations of saving, motherhood, technologies, care, safety, risk and medical authority. Different techniques foreground particular properties of the milk, as ultimately a set of moral decisions converges around saving, securing and sustaining life, materialising relationships and forming the milk form one entity into another and back again.